Pengembangan Media Pembelajaran Flashcard Augmented Reality Berbasis Pembelajaran Berdiferensiasi Untuk Meningkatkan Kemampuan Berpikir Kreatif pada Materi Sistem Pencernaan - Desy Aulia Faricha (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study aimed to develop a differentiated learning–based Augmented Reality (AR) flashcard learning media and to examine its validity, practicality, and effectiveness in improving students’ creative thinking skills on the digestive system topic in senior high school. Biology learning requires active student involvement; however, conventional media and uniform learning approaches have not fully accommodated differences in students’ learning readiness, which may hinder the development of creative thinking skills. This research employed a Research and Development (R&D) method using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. The research subjects were senior high school students. Data were collected through expert validation sheets, student response questionnaires, learning implementation observation sheets, and pretest posttest instruments measuring creative thinking skills and learning outcomes. Data were analyzed using descriptive qualitative and quantitative techniques, including N-Gain analysis to determine learning effectiveness. The results showed that the differentiated learnin based AR flashcard media met the criteria of being valid and practical for use in biology learning. Furthermore, the implementation of the developed media effectively improved students’ creative thinking skills, as indicated by an increase in pretest and posttest scores with moderate to high N Gain categories. In addition, the media also contributed positively to students’ learning outcomes and learning mastery. Therefore, the differentiated learningbased AR flashcard media is feasible and effective as an innovative learning medium to support the development of creative thinking skills in senior high school biology learning.
:: Finalisasi Repositori File 3 Juni 2026_Kurnadi
Keywords: biology learning innovation; cognitive flexibility; instructional design model; learner readiness; research and development